Here's the question you clicked on:
Haleyy_Bugg
The graph of which equation is shown below?
y = −x^2 + 2x − 3 y = −x^2 − 2x − 3 y = x^2 + 2x − 3 y = x^2 − 2x − 3
the first answer choice The roots of the equation are found anywhere the equation y=x^2-2x-3 is equal to zero, like the question states. To do this you must first factor the equation. x^2 is easy enough, it splits into two x's, so you start with: (x )(x ) Now you have to find the combinations that multiply to give -3 and who's sum is -3. We can use +1 and -3, giving us: (x+1)(x-3) = 0 We can make the equation equal to zero by making either of two brackets equal to zero, so the equation's roots lie at x=-1 and x=3.